Respuestas

  • Usuario de Brainly
2013-12-02T21:01:43+01:00
(*)              4y = 3 + x
               => 4y - x =3

Entonces:

3 =  - x + 4y ............. (i)
10=3x+7y ..............(ii)

Multiplicando a (i) por 3

9 = -3x + 12y
10 = 3x + 7y        .............. sumamos ambas ecuaciones y nos queda:
19 = 0x + 19y
19/19 = y
1 = y


Luego, si y=1 , reemplazando en (i)  3 =  - x + 4y
                                                      3 = -x + 4(1)
                                                        x =1


Respuesta: x=1  ; y=1

Eso es todo!!